Hyaluronan, CD44, and Emmprin Regulate Lactate Efflux and Membrane Localization of Monocarboxylate Transporters in Human Breast Carcinoma Cells - Slomiany, Mark G. (2009)
Interactions of hyaluronan with CD44 in tumor cells play important cooperative roles in various aspects of malignancy and drug resistance. Emmprin (CD147; basigin)is a cell surface glycoprotein of the immunoglobulin superfamily that is highly up-regulated in malignant cancer cells and stimulates hyaluronan production, as well as several downstream signaling pathways. Emmprin also interacts with various monocarboxylate transporters (MCT). Malignant cancer cells use the glycolytic pathway and require MCTs to efflux lactate that results from glycolysis. Glycolysis and lactate secretion contribute to malignant cell behaviors and drug resistance in tumor cells. In the present study, we find that perturbation of endogenous hyaluronan, using small hyaluronan oligosaccharides, rapidly inhibits lactate efflux from breast carcinoma cells; down-regulation of emmprin, using emmprin small interfering RNA, also results in decreased efflux. In addition, we find that CD44 coimmunoprecipitates with MCT1, MCT4, and emmprin and colocalizes with these proteins at the plasma membrane. Moreover, after treatment of the cells with hyaluronan oligosaccharides, CD44, MCT1, and MCT4 become localized intracellularly whereas emmprin remains at the cell membrane. Together, these data indicate that constitutive interactions among hyaluronan, CD44, and emmprin contribute to regulation of MCT localization and function in the plasma membrane of breast carcinoma cells.